Caracterização de mutantes de Streptomyces clavuligerus ATCC 27064 obtidos por aplicação de radiação UV e tratamento químico - Vasconcelos, Eliton da Silva (Universidade Federal de São Carlos, 2008)
The clavulanic acid is a powerful inhibitor of the beta-lactamases produced by bacterias resistants to penicillin and cefalosporin. This acid is produced industrially by strains of Streptomyces clavuligerus in complex medium whose carbon and nitrogen source are supplied by inexpensive substances that provide high production. The clavulanic acid has a high affinity for enzymes that attach to penicillin derivatives, what enable to be used with semi-synthetic penicillin, being the combination with amoxilin the best exemple of substances inhibitor of beta-lactamases. The genetic improvement using physical and chemical agents is a necessary strategy in programs of production of bioactive metabolit whereas the industrial strains lost its productivity due phenomenon of genetic instability. In this work it appraised morphologic and biochemistry characteristic of some mutant strains obtained by treatment with UV light and with MMS, always comparing the caracteristics of the mutants with the wild type (Streptomyces clavuligerus ATCC 27064). The results indicated that the mutations originated strains with differents phenotypes, and the larger changes were demonstrated through mutants strains AC116, MMS 150 and MMS 54, that exhibited absence of pigmentation in its mature spores. The strains MMS 150 presented a larger production of AC when cultured in semisynthetics mediums. Among the others mediums the wild type strain obtained a larger production, however when used the modifed complex medium, the MMS 150 strain showed changes in its lipolitic activity and a larger production of AC.
Keywords: Microbiologia industrial; Ácido clavulânico; Streptomyces clavuligerus; Caracterização morfológica; NAO CATEGORIZADO